Clonal evolution analysis of paired anaplastic and well‐differentiated thyroid carcinomas reveals shared common ancestor. Issue 12 (24th September 2018) - Dong, Weilai; Nicolson, Norman G.; Choi, Jungmin; Barbieri, Andrea L.; Kunstman, John W.; Abou Azar, Sara; Knight, James; Bilguvar, Kaya; Mane, Shrikant M.; Lifton, Richard P.; Korah, Reju; Carling, Tobias
Abstract: Foci of papillary or follicular thyroid carcinoma are frequently noted in thyroidectomy specimens of anaplastic thyroid carcinoma (ATC). However, whether ATCs evolve from these co‐existing well‐differentiated thyroid carcinomas (WDTCs) has not been well‐understood. To investigate the progression of ATC in patients with co‐existing WDTCs, five ATC tumors with co‐existing WDTCs and matching normal tissues were whole‐exome sequenced. After mapping the somatic alteration landscape, evolutionary lineages were constructed by sub‐clone analysis. Though each tumor harbored at least some unique private mutations, all five ATCs demonstrated numerous overlapping mutations with matched WDTCs. Clonal analysis further demonstrated that each ATC/WDTC pair shared a common ancestor, with some pairs diverging early in their evolution and others in which the ATC seems to arise directly from a sub‐clone of the WDTC. Though the precise lineal relationship remains ambiguous, based on the genetic relationship, our study clearly suggests a shared origin of ATC and WDTC.